2018
DOI: 10.1093/jcr/ucy047
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Deceleration

Abstract: People increasingly seek out opportunities to escape from a sped-up pace of life by engaging in slow forms of consumption. Drawing from the theory of social acceleration, we explore how consumers can experience and achieve a slowed-down experience of time through consumption. To do so, we ethnographically study the Camino de Santiago pilgrimage in Spain and introduce the concept of consumer deceleration. Consumer deceleration is a perception of a slowed-down temporal experience achieved via a decrease in certa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
152
3
18

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(179 citation statements)
references
References 30 publications
6
152
3
18
Order By: Relevance
“…Together, the two articles add a novel, embodied perspective to research on consumer spiritualty. Previous research has shown that painful bodies can be a powerful vehicle to slow down consumers' minds (Husemann & Eckhardt, 2018) as well as to enable consumers to escape the self and help create the story of a fulfilled life (Scott, Cayla, & Cova, 2017). These two articles add that, via the body or bodily sensations such as pain, consumers can actualise a spiritual experience.…”
Section: Embodiment and Consumer Spiritualitymentioning
confidence: 99%
See 3 more Smart Citations
“…Together, the two articles add a novel, embodied perspective to research on consumer spiritualty. Previous research has shown that painful bodies can be a powerful vehicle to slow down consumers' minds (Husemann & Eckhardt, 2018) as well as to enable consumers to escape the self and help create the story of a fulfilled life (Scott, Cayla, & Cova, 2017). These two articles add that, via the body or bodily sensations such as pain, consumers can actualise a spiritual experience.…”
Section: Embodiment and Consumer Spiritualitymentioning
confidence: 99%
“…Recent consumer research on pilgrimage has discussed the use of technology in search of spirituality with mixed results. Whereas pilgrims' search for practical information in online forums (Husemann & Eckhardt, 2018) as well as online word-of-mouth about sacred sites (Hamilton & Higgins, 2016) can facilitate and promote the spiritual journey, research has shown that pilgrims need to control their technological engagement while travelling to keep the modern world at bay, and thus, be able to truly immerse into the pilgrimage experience (Husemann & Eckhardt, 2018). Van Laer and Izberk-Bilgin's study adds to the theorisation of the relationship between technology and consumer spirituality by showing that, in the aftermath of a pilgrimage, narrating and rating the pilgrimage experience in online reviews can extend the spiritual beyond the physical journey.…”
Section: Technology and Consumer Spiritualitymentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, we know that navigating moral complexity is difficult for consumers (Devinney et al 2010;Geisler and Veresiu 2014;Henry 2010;Luedicke et al 2010) and recent scholarship has indicated that consumers are tasked with the 'impossible': 'to enjoy, provide, realize yourself, be authentic but also recycle, protect workers in China, prevent illegal arms trading, end the killing of animals, and so on, all in order to save capitalism from digging its own grave', (Carrington et al 2016, p. 32). Therein, calls to 'downshift', 'voluntary simplify' and 'decelerate' affluent consumer lifestyles (Etzioni 1998;Husemann and Eckhardt 2018;Schor 1998), alongside other morally moderating behaviours such as 'ethical consumption' (Devinney et al 2010), suggest that a dichotomy might exist between morality and pleasure; the emphasis of "hedonic, self-interested outcomes, in contrast to the more societal-centered viewpoint of ethical consumers", Shiu 2003, p. 1485). Alongside illuminating the process of ethical decision making, alternative hedonism would instead view pleasure and morality as two sides of the same coin, rather than diametric opposites (Shaw and Shiu 2003).…”
Section: Alternative Hedonismmentioning
confidence: 99%